CONCEPTUAL METAPHOR IN RUSSIAN: COLOR AND EMOTION DOMAINS - Qadamboyeva Muhayyo Ravshanbek qizi (TADQIQOTLAR, 2026)
Abstract This article examines the intersection of color and emotion in Russian conceptual metaphor, drawing on lexical data from Metaphors in Russian — Animals, Colors, Emotions, Sports (Bobrova, Kisselev & Lantolf, 2018). Using Conceptual Metaphor Theory (Lakoff & Johnson, 1980) as its analytical framework, the study investigates how color terms in Russian encode abstract cultural values and how the four emotions catalogued in the dictionary — anger, happiness, love, and sadness — recruit multiple structurally distinct source domains. A central finding is that the two domains are not independent: red, white, black, and green each appear within emotion metaphors as markers of observable physiological states, creating a cross-domain color-emotion interface grounded in the visible bodily correlates of arousal. At the same time, culturally specific elaborations — particularly the density of black-color illegality metaphors and the Orthodox-inflected anger expressions — demonstrate that embodied universals are always shaped by historical and cultural experience. The article concludes with brief reflections on the implications for advanced Russian language pedagogy.